2023
DOI: 10.2196/44479
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anthropomorphic Cues on Patients’ Perceived Anthropomorphism, Social Presence, Trust Building, and Acceptance of Health Care Conversational Agents: Within-Subject Web-Based Experiment

Abstract: Background The last decade has witnessed the rapid development of health care conversational agents (CAs); however, there are still great challenges in making health care CAs trustworthy and acceptable to patients. Objective Focusing on intelligent guidance CAs, a type of health care CA for web-based patient triage, this study aims to investigate how anthropomorphic cues influence patients’ perceived anthropomorphism and social presence of such CAs and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…Similarly, another study demonstrated that an augmented human-like embodiment of a digital avatar resulted in greater social closeness among the participants [ 116 ]. Correspondingly, strong social presence and emotional closeness are regarded as key facilitators of favorable attitudinal and behavioral outcomes among users [ 117 ]. Hence, anthropomorphism positively correlates to users’ perceived trust and acceptance of a virtual agent [ 12 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another study demonstrated that an augmented human-like embodiment of a digital avatar resulted in greater social closeness among the participants [ 116 ]. Correspondingly, strong social presence and emotional closeness are regarded as key facilitators of favorable attitudinal and behavioral outcomes among users [ 117 ]. Hence, anthropomorphism positively correlates to users’ perceived trust and acceptance of a virtual agent [ 12 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, strong social presence and emotional closeness are regarded as key facilitators of favorable attitudinal and behavioral outcomes among users [ 117 ]. Hence, anthropomorphism positively correlates to users’ perceived trust and acceptance of a virtual agent [ 12 , 117 ]. Indeed, digital human faces as intelligent CAs are considerably promising for achieving a human-like presence to enhance human-machine interaction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%